Harry potter and the deathly hallows part 2 - Rickman, Alan.; Smith, Maggie; Fiennes, Ralph; Gambon, Michael; Radcliffe, Daniel; Grint, Rupert; Watson, Emma. ([United States] : Warner Home Video, 2011)
In the epic finale, the battle between the good and evil forces of the wizarding world escalates into an all-out war. The stakes have never been higher and no one is safe. But it is Harry who may be called upon to make the ultimate sacrifice as he draws closer to the climactic showdown with Lord Voldemort. It all ends here.
"Part II gets everything right to send off Harry on a cinematic high."--Pete Hammond, Boxoffice Magazine.
"Everything a summer blockbuster should be but rarely is - a whip-smart, slam-bang piece of entertainment where we deeply care about the fate of the central characters."--Lou Lumenick, New York Post.
"The thrilling conclusion to a phenomenal cinematic story 10 years in the telling, Harry Potter and the Deathly Hallows - Part 2 is proof that authentic movie excitement is its own form of magic."--Lisa Schwarzbaum, Entertainment Weekly.
Director, David Yates.
Alan Rickman, Michael Gambon, Rupert Grint, Emma Watson, Ralph Fiennes, Maggie Smith, Daniel Radcliffe.
MPAA rating: PG-13.
DVD.
English audio.
English subtitles for the deaf and hard of hearing.
Keywords: Fantasy; Award Winners; Action / Adventure; Adventure